Mental Health Disorders Associated with Sinonasal and Skull Base Malignancies: A Large Cohort Study - Lee, Ji Hyae; Zacharia, Brad E.; Ba, Djibril; Leslie, Douglas; Liu, Guodong; Goyal, Neerav (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The main purpose of this article is to examine the prevalence, incidence, sociodemographic, and clinical characteristics of mental health disorders (MHDs) among patients with skull base malignancies.Design Retrospective cohort study.Settings/Participants Six-thousand seven-hundred sixty sinonasal/skull base cancer patients in the MarketScan database between 2005 and 2014.Main Outcome Measures Frequency of MHDs pre- and post-diagnosis in patients harboring sinonasal/skull base malignancies.Results A significant increase in MHDs was noted from pre- to post-cancer diagnosis (22 vs 31%, p < 0.0001). Despite an increase in the prevalence rate, the demographic profile of patients with MHDs post-diagnosis remained similar to pre-diagnosis. Those patients harboring MHDs were, however, more likely to be women (62.7 vs 47.4%), and carry a history of smoking (40.9 vs 26.3%) than those without MHDs. These comparisons were statistically significant (p < 0.0001).Conclusion The prevalence of MHDs increases following a diagnosis of a sinonasal/skull base malignancy. Patients with MHDs were more likely to be women and smokers.
Keywords: sinonasal cancer; skull base cancer; mental health disorders; survivorship